The Potential Benefits of Non-skills Training (Mental Toughness) for Elite Athletes: Coping With the Negative Psychological Effects of the COVID-19 Pandemic - Dagnall, Neil; Drinkwater, Kenneth Graham; Denovan, Andrew; Walsh, R. Stephen (Frontiers in Sports and Active Living, 2021)
The spread of COVID-19 has had a significant impact on global sport. This is especially true at the elite level, where it has caused the cancellation of competition and prevented participation in routine training. Also, restrictions have disrupted long-term schedules and future event planning. Consequently, many elite athletes remain unsure when they will return to full competition, what form it will take, and worry about further interruptions. Although some athletes have successfully adapted to the demands of the COVID-19 crisis, many have struggled to adjust. This has resulted in psychological difficulties such as increased stress, anxiety and depression. This paper critically examines the extent to which non-cognitive skills training, in the form of Mental Toughness, can help elite athletes inoculate against and cope with adverse psychological effects arising from the COVID-19 pandemic. Non-cognitive skills encompass intrapersonal (motivations, learning strategies, and self-regulation) and interpersonal (interactions with others) domains not directly affected by intellectual capacity. Previous research indicates that enhancement of these spheres can aid performance and enhance mental well-being. Moreover, it also suggests that non-cognitive skills training can improve the ability to cope with the challenges of COVID-19. In this context, Mental Toughness encompasses a broad set of enabling attributes (i.e., inherent and evolved values, attitudes, emotions, and cognitions). Indeed, academics commonly regard Mental Toughness as a resistance resource that protects against stress. Accordingly, this article discusses the use of the 4Cs (Challenge, Commitment, Control, and Confidence), multi-dimensional model to counter negative psychological effects arising from COVID-19.